Screening and aroma-producing characteristics of ester aroma-producing yeast from medium- and high-temperature Daqu - DING Changhe, WAN Haowei, WEI Shuyin, FAN Xing, FAN Duoduo (Zhongguo niangzao)
In this study, the ester aroma-producing yeast strains were isolated and screened from medium- and high-temperature Daqu samples by traditional culture isolation method combined with the olfactory method, and identified by molecular biology techniques, and their growth characteristics and aroma-producing characteristics were analyzed. The results showed that 5 representative strains of ester aroma-producing yeasts, numbered G-8, Z-3, G-1, G-2 and G-3, were screened and identified as Saccharomycopsis fibuligera, Wickerhamomyces anomalus, Pichia kudriavzevii, Meyerozyma caribbica and Naganishia diffluens, respectively. Among them, the strain Z-3 grew ripidly and had better tolerance and the optimal effect on increasing the content of volatile flavor substances, which could tolerate 13% (V/V) ethanol, 70% glucose and 1.0% (V/V) acetic acid. A total of 21 volatile flavor compounds were detected from the solid-state fermentation product of strain Z-3, and the total content was 197.13 μg/g. Among them, 8 key volatile flavor compounds were screened according to odor activity value (OAV)>1, including ethyl acetate, isoamyl acetate and so on, indicating that the strain Z-3 had good application potential in improving Baijiu flavor.